Co0.5Zn0.5Fe2O4/Ag3PO4: A magnetic, highly efficient visible-light photocatalyst and the Z-scheme mechanism for removal of anionic dye and tetracycline hydrochloride. (1st August 2018) - Lin, Cuiping; Xie, Xin; Li, Chen; Yan, Qishe
Abstract: The magnetic Co0.5 Zn0.5 Fe2 O4 incorporated Ag3 PO4 photocatalysts were fabricated by facile sol-gel and hydrothermal route. The resulting Co0.5 Zn0.5 Fe2 O4 /Ag3 PO4 composites were characterized by XRD, 1 SEM, 2 UV–vis DRS, 3 FT-IR 4 and VSM. 5 The results indicated that the magnetically separable composites with good dispersity showed a strong absorption in the uv–vis region and the saturation magnetization was 85.25 emu g −1 . Anionic dye methyl orange (MO) and tetracycline hydrochloride (TCH) were used to evaluate the activity of the photocatalysts. The result revealed that the magnetic composites exhibited enhanced photocatalytic activity and stability under the visible light irradiation. The ·OH and ·O2 - radicals were found to be the major active species during the photodegradation of TCH, while·O2 - played the important role in photodegrading MO. And a Z-scheme mechanism for the enhanced photocatalytic process was proposed.